THE RELATIONSHIP OF PHARMACEUTICAL SERVICES TO PATIENT SATISFACTION AT THE PUSKESMAS TRADING BANDAR DISTRICT SIMALUNGUN DISTRICT - Yulia Delfahedah; Arsiaty (PT. Radja Intercontinental Publishing, 2022)
The research entitled The Relationship of Pharmaceutical Services to Patient Satisfaction at the Trading Health Center, Bandar District, Simalungun Regency was conducted in July - August 2019. The purpose of this study was to find out how the application of pharmaceutical service standards at the Puskesmas, the level of patient satisfaction and the effect of applying pharmaceutical service standards on satisfaction Patients This research is a descriptive survey research that is cross-sectional. Data collection was carried out by observation by researchers to find out the application of pharmaceutical service standards and to conduct interviews with patients to determine the level of satisfaction with pharmaceutical services. Data was collected from 170 respondents in July-August 2019 at the Trading Health Center, Bandar District, Simalungun Regency, The application of pharmaceutical service standards studied in this study is human resources, facilities and infrastructure for the management of drugs and medical consumables, clinical pharmacy services and service quality control. The criteria for measuring the level of satisfaction include five variables, namely reliability, responsiveness, confidence, empathy and tangible facilities. The results showed that the implementation of pharmaceutical service standards at the Commercial Health Center, namely the application of pharmaceutical service standards at the Commercial Health Center, was included in the less category. Based on the average value of total patient satisfaction, the level of patient satisfaction at the Jawa Maraja Health Center was included in the satisfied category. The application of pharmaceutical service standards at the Commercial Health Center to patient satisfaction with the Mann-Whiteney Test obtained a sig value of <0.05.